Case report: Fibrous dysplasia of the navicular bone treated with excision of navicular and talo-cuneiform arthrodesis. Issue 1 (March 2015) - Siu, W.; Ferguson, K.B.; Kumar, C.S.; Mahendra, A.
Abstract Fibrous dysplasia is an uncommon beningn disorder of bone. It usually affects the long bones, and is uncommon in the navicular. We describe a case of fibrous dysplasia of the navicular successfully treated with navicular excision and talo-cuneiform arthrodesis.